Sustainable and Clean Energy Production Technologies - Pal, Dan Bahadur; Jha, Jay Mant. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This edited book is a comprehensive collection of chapters on various clean energy technology such as solar energy, waste biomass as energy, hydro-electricity generation, biodiesel production from biomass and strategies to cater the demand of clean renewable energy. Clean energy technologies also enhance economic growth by increasing the supply of energy demand and tackling environmental challenges and their impacts due to the use of other conventional sources of energy. The conventional/non-conventional energy production methods are efficient but it has adverse effects on environment and human health. As environmental concerns are not avoidable therefore the necessity of clean energy production comes in to the picture. The clean energy can be produced by different wastes which are caused for the environmental pollution. This book covers various aspects of new and renewable clean energy production technology and its utilization in different fields. This is a useful reading material for students and researchers involved in clean energy study.
Chapter 1. Tiny Renewable Engines: Microalgae and Cyanobacteria as biofuel providers -- Chapter 2. Different Energy Management Strategies for Clean Energy -- Chapter 3. Recycle of Plastic Waste to Liquid Fuel: A sustainable energy production -- Chapter 4. Nanomaterials for Energy Storage Applications -- Chapter 5. Biomass Energy Conversion using Thermochemical and Biochemical Technologies -- Chapter 6. Pyrolysis of waste biomass using solar energy for Clean Energy Production -- Chapter 7. Biomass Digestion for Production of Electrical Energy -- Chapter 8. Solar Energy Conversion Techniques and Practical Approaches to Design Solar PV Power Station -- Chapter 9. Recent Advancement in Preparation Strategy of Efficient Graphene-Cds Based Photocatalysts for H2 Production by Water Splitting -- Chapter 10. Design and Storage of Solar Thermal Energy Production -- Chapter 11. Clean Energy using Hydroelectric generation from Rivers -- Chapter 12. Clean Energy Production using Solar Energy Resources.
Keywords: Microbiology; Renewable energy sources; Microbiology; Renewable Energy